(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
Radicalism has recently become an interesting discourse, where the existence of radicalism is a central issue in the opinion of Nahdlatul Ulama. The purpose of this research is to find out the role of Nahdlatul Ulama in couneteracting radicalism. This study uses Roxanne L Euben theory of radicalism which is used to dissect the phenomenon of radicalism and Robert Hefner civil society theory which is used to explain the role of Nahdlatul Ulama as a civil society group in the field. This study uses a qualitative research method with a phenomenological approch. The results of this study show that radicalism in the interpretation of Nahdlatul Ulama has a tone such as thearts, violence, acts of terrorism and efforts made by Nahdlatul Ulama in preventing and reducing radicalism from developing.